An Organizational Case Study of Mental Models among Health System Leaders during Early-Stage Implementation of a Population Health Approach - Terpou BA; Bird M; Srinivasan D; Bains S; Rosella LC; Desveaux L (Dove Medical Press, 2024)
Braeden A Terpou,1 Marissa Bird,1,2 Diya Srinivasan,1 Shalu Bains,3 Laura C Rosella,1,4 Laura Desveaux1,2 1Institute for Better Health, Trillium Health Partners, Mississauga, Ontario, Canada; 2Institute of Health Policy, Management, and Evaluation, University of Toronto, Toronto, Ontario, Canada; 3Mississauga Hospital, Trillium Health Partners, Mississauga, Ontario, Canada; 4Dalla Lana School of Public Health, University of Toronto, Toronto, Ontario, CanadaCorrespondence: Laura Desveaux, Institute for Better Health, Trillium Health Partners, 2085 Hurontario Street, Mississauga, ON, L5B 1B8, Canada, Tel +1 437772-6836, Email Laura.Desveaux@thp.caPurpose: As the COVID-19 pandemic recedes, the importance of population health has come into sharp focus, prompting many health systems to explore leveraging population health data (PHD) for operational planning. This approach requires that healthcare leaders embrace the dual priorities of maintaining excellence in patient care while promoting the overall health of populations. However, many leaders are new to population-based thinking, posing a threat to successful operationalization if mental models are not aligned.Patients and Methods: This qualitative case study explored the alignment of mental models among 13 senior leaders at Trillium Health Partners (THP), one of Canada's largest community hospitals, as they embark on embedding PHD within operational workflows.Results: All leaders recognized the necessity of adopting a population health approach amid resource constraints and growing pressures. When discussing the operationalization of PHD, two distinct mental models emerged among leaders: one focused on patient care and the other on population health. While executive leaders demonstrated a fluidity in their thinking between the two, programmatic leaders favoured one over the other. For example, some viewed the organization's focus on PHD as competing with their patient care responsibilities, while others saw the use of PHD as a solution to the organization's operational pressures. Despite these divergences, leaders unanimously stressed the importance of increasing the organization's risk tolerance and devolving decision-making as a necessary precursor to realizing the transformation to a PHD-driven approach.Conclusion: These divergent mental models highlight a need to clarify the shared vision for the use of PHD along with its impact on leadership roles and accountabilities. These findings illustrate the current state from which THP aims to evolve and underscore the importance of aligning leaders' mental models as a critical step to facilitating successful integration of PHD and advancing a collective vision for healthcare transformation.Keywords: health equity, population health management, healthcare leaders, qualitative study